Quantitative evaluation of dual-channel drug supply policy on nationally negotiated anti-tumor drugs in Xuzhou: based on interrupted time series analysis - Qin, Zhaohui; Xu, Shuo; Li, Qi; Guan, Xueling; He, Meng; Zhou, Min; Xu, Yan (Frontiers in Pharmacology, 2025)
IntroductionIn September 2021, the “dual-channel” supply policy for anti-tumor drugs had launched in China. This policy solved the problem of difficult and expensive access to anti-tumor drugs. This study aims to measure the impacts of the dual-channel policy on indicators of availability, cost, and reimbursement ratio.MethodsThis study adopt the interrupted time series analysis method and selects data on anti-tumor drug payments from October 2020 to October 2022 in Xuzhou City for analysis.ResultsAfter September 2021, the cost of anti-tumor drugs has increased significantly, and the number of purchases and reimbursement ratio and other indicators have increased. It is worth noting that the changes in urban and rural residents’ health insurance are more significant than those of employees’ health insurance.DiscussionThe “dual-channel” supply policy has greatly improved accessibility to anti-tumor drugs. It also reduced the financial burden of disease for ordinary residents. Therefore, we need to enhance the sufficiency of policy implementation.